Clinico-laboratory profile of breath-holding spells in children in Sohag University Hospital, Upper Egypt - Sadek, Abdelrahim Abdrabou (Electron Physician, 2016)
INTRODUCTION: Breath-holding spells (BHSs) are involuntary pauses of breathing, sometimes accompanied by loss of consciousness. They usually occur in response to an upsetting or surprising situation. Breath-holding spells are usually caused by either a change in the usual breathing pattern or a slowing of the heart rate. In some children, BHSs may be related to iron deficiency anemia. The aim of the work was to study the clinical and laboratory profile of BPHs in children presented to the Neuropediatric Clinic at Sohag University Hospital. METHODS: An observational prospective study was done at Sohag University Hospital over a period of one year on children diagnosed as having BHSs by clinical history and laboratory evaluation, including complete blood count (CBC), serum iron, serum ferritin, total iron binding capacity, and Electroencephalography (EEG). RESULTS: During the period of study (one year), we reviewed data of 32 children who had been diagnosed as having BHSs. We found that cyanotic spells (71.88%) predominated over pallid spells. There were positive family histories (31.25%) and consanguinity (53.135) in the studied patients. We found a high incidence of iron deficiency anemia (62.5%) in association with BHS. Abnormal EEGs were found in (65.63%) of studied children. CONCLUSION: BHS is a common, important problem associated with iron deficiency anemia, which is, in turn, a common nutritional problem in our country.